Pathogenicity of Bordetella bronchiseptica local isolate in piggeries - Siti Chotiah; Tarmudji . (Jurnal Ilmu Ternak dan Veteriner, 2007)
Bordetella bronchiseptica causes respiratory tract infections in many animals species. The bacteria were isolated and identified from piggeries in Indonesia. The aim of this study was to define the pathogenicity of B. bronchiseptica local isolate. Thirty piglets less than a week old were divided into 6 treatment groups. Each group of five was infected with Bordetella bronchiseptica BS9 (BCC B2455) local isolate with dose of 4.2 x 105, 4.2 x 106, 4.2 x 107, 4.2 x 108, 4.2 x 109 dan 4.2 x 1010 CFU/ml respectively by intra nasal inoculation, and three piglets were used as the control. The clinical signs, reisolation of bacteria, and histopathological changes were observed. The result showed that all treatment groups showed clinical sign of serous nasal discharge, and sneezing only found in two groups. Reisolation of those bacteria from concha were found in all groups, from trachea in one group, from bronchus in all groups, and they were not found in the control group. Histopathological change of epithelial cells desquamation and lost of cillias on concha were found in all treatment groups. On the trachea, epithelial cells desquamation were found in 3 treatment groups and lost of cillias in 4 treatment groups. On the bronchus, epithelial cells desquamation were found in 2 treatment groups and lost of cillias were found in 3 treatment groups. Total piglet that showed clinical phenomenon, positive bacteria reisolation and histopathological change from each group were not proportion to the dose given. This study showed that the local isolate of B. bronchiseptica was pathogenic because it can cause the damage of ciliated cylindrical epithelial cells of the upper respiratory tract. Key Words: Bordetella bronchiseptica, Local Isolate, Pathogenicity, Piglet